Gamified Website Design for Calisthenics Workouts Enhancing Motivation and User Engagement - Gregorius Lai; Istiono, Wirawan (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2025)
Workout is one way to adopt a healthy lifestyle. Workout can minimize disease, one of which is obesity. Even though it has great benefits, there are still many people who don’t exercise regularly. Therefore, sports activities need to be increased. One sport that does not require equipment is gymnastics. Gymnastics training is a physical activity that is as beneficial as the gym. One way to help increase motivation is to do gamification. Gamification can increase motivation and make boring things more interesting. In this research, a calisthenics workout website was designed and created using the gamification method. Website was evaluated by 33 people. Based on the survey conducted, the curiosity value was 83.32%, the perceived ease of use value was 79%, the perceived usefulness value was 83.32%, the joy value of 80.6%, behavioral intention to use value of 83.03%, focused immersion value of 80.53%. The final average obtained from all categories is 81.12%.